Optimizing 2-nitrophenol and chromium adsorption from water with aluminium oxide via response surface methodology - Asmaly, Hamza A.; Kabbashi, Nassereldeen Ahmed; Al-Khatib, Ma'an Fahmi Rashid; Alam, Md. Zahangir; Mohd Khairuddin, Nur Farahah (2024)
The study explored the efficacy of an innovative adsorbent crafted from carbon nanotubes and carbon nano fibbers integrated with aluminium oxide, in purging water solutions of both organic (2-Nitrophenol) and inorganic (Chromium III) contaminants. The study refined the aluminium impregnation method to boost the adsorption efficiency of CNAs/Al2O3 in removing certain pollutants. Through a central composite design (CCD) strategy, optimal adsorption conditions were determined. The most effective removal of 2-NPh (2-Nitrophenol) and Cr3+ (Chromium III) occurred with CNAs/Al2O3 at an 18% impregnation ratio, after 3 hours of ultrasonication and calcination Temperature at 300◦C. This technique yielded adsorption capacities of 82.02mg/g for 2-NPh and 96.57mg/g for Cr3+. The aluminium content in the adsorbents, prepared under these specified conditions, was verified, and measured using EDX (Energy Dispersive X-ray) analysis. Further, BET (Brunauer-Emmett-Teller) measurements revealed the impact of aluminium ratios on the surface area of CNAs/Al2O3, where an 18% aluminium ratio led to a surface area of 176 m2/g, diminishing to 125 m2/g and 110 m2/g for 20% and 22% aluminium ratios, respectively. The Predicted adsorption capacity for 2-NPh was estimated at 83.154mg/g, aligning closely with the observed 82.02mg/g, while the estimate for Cr3+ at 97.80mg/g nearly matched the actual 96.57mg/g. A validation study evaluated the predicted adsorption capacities for both contaminants, finding that the actual capacities were 86.79mg/g for 2 – NPh and 99.79mg/gfor Cr3+. The study noted an acceptable error margin in optimal adsorption capacity of about 4.5% for 2 – NPh and 2% for Cr3+. The optimized integration of metal oxides with CNAs through impregnation significantly enhances their efficacy in removing pollutants, particularly when aluminium oxide is used to boost their capacity for purifying wastewater by extracting both organic and heavy metal contaminants.